Supplement for the genus Phlugiolopsis Zeuner, 1940 (Orthoptera: Tettigoniidae: Meconematinae) from China - Bian, Xun; Shi, Fu-Ming; Chang, Yan-Lin (Zootaxa, 2012)
During curation of some species from Guangxi, China and discovered 2 new species, as: Phlugiolopsis damingshanisBian, Shi & Chang sp. nov. and Phlugiolopsis huangi Bian, Shi & Chang sp. nov.. Therefore, this paper is a supplement for Phlugiolopsis (Bian, Shi & Chang, 2012). The type specimens are deposited in the Museum of Hebei University.